A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species - Wilbert, Norbert; Song, Weibo (Journal of Natural History, 2008)
Wilbert, Norbert, Song, Weibo (2008): A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species. Journal of Natural History 42 (13-14): 979-1012, DOI:10.1080/00222930701877540, URL: http://dx.doi.org/10.1080/00222930701877540